Factors Associated With the Presence of Foveal Bulge in Eyes With Resolved Diabetic Macular Edema - Wu, Qiaowei; Hu, Yijun; Liu, Baoyi; Lin, Zhanjie; Xiao, Yu; Zeng, Xiaomin; Fang, Ying; Yan, Ying; Ye, Ya; Yan, Ming; Huang, Zhen; Yu, Honghua; et al. (Frontiers in Medicine, 2022)
Purpose: To evaluate factors associated with the presence of foveal bulge (FB) in resolved diabetic macular edema (DME) eyes. Methods: A total of 165 eyes with complete integrity of ellipsoid zone at the fovea and resolved DME were divided into two groups according to the presence of FB at 6 months after intravitreal injection of ranibizumab treatment. Best-corrected visual acuity (BCVA), central foveal thickness (CFT), outer nuclear layer (ONL) thickness, height of serous retinal detachment (SRD) and non-SRD, and inner segment (IS) and outer segment (OS) length of the two groups were measured and compared at baseline and each follow-up. The correlations between the presence of FB and pre- and post-treatment factors were determined by logistic regression analysis. Results: At baseline, BCVA was significantly better, and CFT and incidence and height of SRD were significantly lower in the FB (+) group (all P < 0.05). At 6 months, FB was present in 65 (39.39%) eyes. Post-treatment BCVA was significantly better and OS length was significantly longer in the FB (+) group at 6 months (all P < 0.05). Multivariate analysis identified younger age, better BCVA, and lower CFT before treatment as significant predictors of the existence of FB at 6 months (all P < 0.05). At 6 months, better BCVA and longer OS length were significantly correlated with the existence of FB (all P < 0.05). Conclusions: Factors associated with the presence of FB after resolution of DME include younger age, better baseline BCVA, and lower baseline CFT, and better post-treatment BCVA and longer post-treatment OS length.